Siblings With Mutations in TRAPPC11 Presenting With Limb-Girdle Muscular Dystrophy 2S. Issue 1 (September 2017) - Fee, Dominic B.; Harmelink, Matthew; Monrad, Priya; Pyzik, Erika
Abstract : Abstract: Limb-girdle muscular dystrophy 2S (LGMD2S) is an autosomal recessive condition due to mutations in the TRAPPC11 gene. It is recently described with only 9 prior reported individuals. In addition to the muscular dystrophy, some affected individuals have small head size, global developmental delay, seizures, cataracts, and liver problems. Siblings with an uncharacterized LGMD were assessed; whole-exome screening revealed compound heterozygous mutations in the TRAPPC11 gene. Their presentation helps confirm the emerging phenotype for LGMD2S. Abstract : Supplemental Digital Content is Available in the Text.